Effect of shading intensity on tuber production of Eleocharis kuroguwai Ohwi - Inamura, T. (Kyoto Univ. (Japan)); Yamamoto, T; Yoshida, H; Sugiyama, T; Nishio, K (Journal of Weed Science and Technology, 2001)
Experiments were carried out in order to obtain information on the practical control of tuber production of Eleocharis kuroguwai Ohwi, a perennial paddy weed. In the experiments, single planting of the weed alone and mixed planting with paddy rice were conducted in paddy fields. The plants were subjected to four levels of light intensity during the tuber formation period (Fig. 3, Table 1), to observe the changes in the dry matter and tuber production associated with the suppression of the radiation absorbed by the weed. Then, the quantitative relation between the shading intensity and tuber production was analyzed. The growth of the stem, the assimilatory organ of the weed, was reduced in proportion to the reduction of the light intensity (Fig. 5). As the stem growth and light intensity decreased, the radiation absorbed during the tuber formation period markedly decreased, and the aboveground weight at the end of the tuber formation period was considerably reduced (Table 1, 2). Along with the reduction of the light intensity, the ratio of the tuber dry matter weight to total dry matter weight (aboveground and tuber dry matter weight) at the end of the tuber formation period (tuber-total dry matter ratio) was reduced (Table 2). Therefore, the total tuber weight was remarkably reduced with the decrease of the intercepted radiation (Fig. 6). However, the average weight of a tuber did not change, as the tuber number decreased in proportion to the reduction of the total tuber weight (Table 2). The contribution rate of accumulated carbohydrates present in the vegetative parts at the tuber initiation stage to the carbohydrates of the tubers at the end of the tuber formation period was estimated to be very low and ranged from 3 to 5% (Fig. 6). It was confirmed that tuber production directly depended on the total dry matter production and the tuber-total dry matter ratio, as indicated in our previous study. When the radiation absorbed during the tuber formation period was reduced to 20% of that in the non-shading control in the single planting of the weed or 40% in the mixed planting, the tuber production depended only on the amount of carbohydrates accumulated in the vegetative parts at the tuber initiation stage. It is concluded that the decrease of the radiation absorbed during the tuber formation period up to 20% of that in the non-shading control in the single planting or 40% in the mixed planting is an effective method of control to reduce tuber reproduction of the perennial weed.